DISPUTE INTERNATIONAL BETWEEN INDONESIA AND MALAYSIA SEIZE ON SIPADAN AND LINGITAN ISLAND - Nur Fareha Binti Mohammad Zukri; Ong Argo Victoria; Fadli Eko Apriliyanto (International Journal of Law Reconstruction, 2019)
In 1998 the issue of Sipadan and Ligitan dispute brought to the ICJ, later in the day Tuesday, December 17, 2002 ICJ issued a decision on the sovereignty dispute case of Sipadan-Ligatan between Indonesia and Malaysia. As a result, in the voting at the institution, Malaysia won by 16 judges, while only one person who sided with Indonesia. Of the 17 judges, 15 are permanent judges of MI, while one judge is an option Malaysia and another selected by Indonesia. Victory Malaysia, therefore under consideration effectivity (Without deciding on the question of territorial waters and maritime boundaries), the British (colonizers Malaysia) has made a real administrative action in the form of the issuance of bird wildlife protection ordinance, a tax levied against turtle egg collection since 1930, and the operation of the lighthouse since the 1960s an. Meanwhile, Malaysia's tourism activities do not be a consideration, as well as the refusal is based on chain of title (a proprietary suite of Sultan of Sulu) but failed to demarcate the sea border between Malaysia and Indonesia in Makassar strait.